Implementasi Model Discovery Learning Berbasis Media Visual dalam Memahami Materi Zakat di MTs Al-Washliyah 48 Binjai - Amru Syahputra Lubis; Alfian Tanjung (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study explores the application of a visual media–assisted Discovery Learning model in zakat instruction at MTs Al-Washliyah 48 Binjai. The study was conducted due to students’ limited understanding of zakat concepts, which was associated with the predominance of teacher-centered instruction. Employing a descriptive qualitative field approach, the research involved Fikih teachers, the madrasah principal, and students as participants. Data were obtained through classroom observation, semi-structured interviews, and documentation, then analyzed using interactive qualitative procedures consisting of data reduction, data display, and conclusion drawing. The results indicate that Discovery Learning was implemented through six instructional phases: stimulation, problem identification, data collection, data processing, verification, and generalization. The integration of visual media (images, videos, and infographics) contributed to higher student engagement and facilitated the comprehension of zakat topics that are conceptually abstract, such as zakat categories, calculation procedures, and distribution. However, several challenges emerged, including limited multimedia facilities, varying teacher readiness, and differences in students’ learning motivation. These challenges were addressed through optimizing available resources, employing low-cost media alternatives, organizing group-based learning, and providing intensified learning assistance.